2021
DOI: 10.3390/molecules26247675
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Potential of Annona muricata Linn. An Edible and Medicinal Plant in Mexico: In Vitro, In Vivo, and Toxicological Studies

Abstract: Annona muricata (Am) is a plant used in traditional Mexican medicine to treat cancer. In this study, ethanol extracts of Am collected in Acapulco and Tecpan from Guerrero state were evaluated orally on Balb/c mice inoculated with 4T1 cells, for cytotoxic activity (CA) on 4T1 cells, in brine shrimp lethality assay (BSLA), and for acute oral toxicity in mice. In addition, ethanol extracts were subjected to high-performance liquid chromatography (HPLC) with diode array detection. Results showed that the extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Our antilymphoma activity results showed a direct correlation with the in vitro cytotoxic activity of the three terpenoids. In addition, and in line with previous studies, we found a correlation of antilymphoma activity and BSL by obtaining LD 50 values of <10 µg mL −1 for FA and PT, and <100 µg mL −1 for PEAm and MTX which were in line with the Gg and PEAm data reported in our previous study [ 2 , 32 ]. These results confirmed that BSL could be used as a practical, economical, and simple tool for obtaining new antitumor agents isolated from plant extracts.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our antilymphoma activity results showed a direct correlation with the in vitro cytotoxic activity of the three terpenoids. In addition, and in line with previous studies, we found a correlation of antilymphoma activity and BSL by obtaining LD 50 values of <10 µg mL −1 for FA and PT, and <100 µg mL −1 for PEAm and MTX which were in line with the Gg and PEAm data reported in our previous study [ 2 , 32 ]. These results confirmed that BSL could be used as a practical, economical, and simple tool for obtaining new antitumor agents isolated from plant extracts.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that Gg (P6), PT (P7) and FA (P10) induced a higher dose-dependent lethality with LD 50 values of <10 µg mL −1 , representing a lethality greater than that of MTX (LD 50 = 24.66 ± 0.27 µg mL −1 ) ( Table 1 ). In line with the findings of previous studies, our results suggested that these molecules might have antitumor potential [ 31 , 32 , 33 ], so we carried out a further investigation of P6, P7 and P10. Later, we characterized P6, P7 and P10 by GC-MS analysis ( Table 2 , Figure 2 and Figure 3 ), focusing on volatile compounds of a terpene nature, since previous studies have reported the presence of acyclic terpenoids in A. macroprophyllata [ 34 ] with antitumor activity [ 2 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The evaluation of the seriated collections shows that the growth state of the leaves changes the flavonoid concentration; this can modify the antidiabetic effect exerted, being higher in the months when the growth is accentuated. In this sense, phytochemical analysis in other studies has demonstrated that the therapeutic effect and composition of extracts vary greatly depending on the site or season of the collection, even in the same country or in consecutive months [ 11 , 45 ]. Although Ac is considered an evergreen species due to the presence of leaves during almost the whole year, the season could modify the number of metabolites in its extracts [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of special phytochemicals to develop novel anti-oxidative, mitochondrial protection, and anti-apoptotic drugs on DA neurons may achieve the purpose of treating or curing PD. Narcissoside (NCS) ( Figure 1 ) is isolated from Sambucus nigra flowers (elderflowers), and has been reported to have several pharmacological activities, such as antioxidant [ 23 , 24 ], anti-inflammatory activities [ 25 ], anti-SARS-CoV-2 [ 26 ], antihypertensive properties [ 27 ], and antitumor potential [ 28 , 29 ]. It also activates TRPV1 channels in dorsal root ganglion sensory neurons linked with pain-accompanied itch [ 30 ].…”
Section: Introductionmentioning
confidence: 99%